STUDENTS’ RECEPTION TOWARDS SEXUAL HARASSMENT CASE OF GEN-Z AT A PRIVATE UNIVERSITY IN DEPOK - Putra, Bakti Abdillah (International Journal of Accounting, Management, Economics and Social Sciences (IJAMESC), 2023)
Sexual harassment could happen everywhere, including workplace and university. This involves any person who has the opportunity to do the misconduct. Information about sexual harassment is now available on many media platforms, whether it is printed or online. As a group of young people who are highly aware of social problems, Gen Z circle have spoken up about this particular issue, starting from their own social network to national level. This study aims to explain the students’ reception towards sexual harassment case on media which took place in a private university in Depok, West Java. The author will lead the discussion into three categories, the causative factors, the forms, and students’ resistance of sexual harassment. The data collected from 122 students involved in focused group discussion and 4 students were interviewed. An article from Indonesian online media regarding sexual harassment was presented and the research allows the student to react to the news. The results show that student participants believe sexual drive is the main factor and any form of sexual harassment could happen if there is not consent. They disagreed if the perpetrator was treated badly like in the news, even though protection for the victim should be prioritized.